Governance of Communicable Disease Control Services : A Case Study and Lessons from India - Das Gupta, Monica (World Bank, Washington, DC, 2014)
The authors study the impact of governance and administrative factors on communicable disease prevention in the Indian state of Karnataka using survey data from administrators, frontline workers, and elected local representatives. They identify a number of key constraints to the effective management of disease control in India, in misaligned incentives, and the institutional arrangements for service delivery. The authors discuss these under five headings: administrative issues; human resource management; horizontal coordination; decentralization, community involvement, and public accountability; and implementation of public health laws and regulations. They find that India's public health system is configured to be highly effective at top-down reactive work, such as bringing disease outbreaks under control, but not for the more routine collaborations required for proactive disease prevention. The authors conclude with policy recommendations that take into account the complexity of India's system of public administration and the need for simple reforms that can be easily implemented.